Animation Video Development Problem Based Learning Based on Material Multiplication for Student Class IV at MIS Tanjung Tiga - Riskyka; Ramadhani Lubis, Renni (Journal of General Education Science, 2024)
This study aim for develop animated videos based problem based learning.research and development. Development model used i.e. 4D development model, ie define, design, develop, and disseminate. But this study only completed at stage develop. Study held in Mis Tanjung Tiga. Subject study that is student class IV, totaling 17 people, consists of of 11 students boy and 6 students woman. Object in this study namely animated videos based problem based learning. Data collection techniques, namely observation, interviews and questionnaires. Based on results from validation that has been carried out by the lecturer expert that is results from the validator ie media expert with percentage 96.68% said very worthy. Validation results expert Language with percentage 92.38% is said to be very feasible. Validation results expert material with percentage 89.75% said worthy. Based on results and discussion before, then can concluded that animated video problem based learning is said to be worthy used in the material for student class IV in Mis Cape Tiga. From the results feasibility of animated videos based problem based learning on the material multiplication for student class IV at Mis Tanjung Tiga said worthy for used.